If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -4x = 26 Solving 23 + -4x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -4x = 26 + -23 Combine like terms: 23 + -23 = 0 0 + -4x = 26 + -23 -4x = 26 + -23 Combine like terms: 26 + -23 = 3 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75
| 45=-y/7 | | 10x-20=-20 | | cos(2x-pi/4)=-(sqrt(2))/2 | | 8x=8(x+12) | | (2b-4)(b+2)= | | -w/4=-60 | | 18x-25x=14 | | tan^-1(350/x) | | -12x+4=-44 | | (3x-5y)+4y= | | 1.7j=2.21 | | -3-(3-3p)= | | 9x^2+15x+9=0 | | 13x-8y=34 | | 32=7+3x | | 7.30(0.600-X)=2X | | 4-9x=-23 | | 5+3(9x-6)= | | 32=7 | | ?t+10=t+4 | | 3/4x+1/8(x-4)=1/4 | | 4+9(a+8)= | | 3/4-1/2b=-7/9 | | 3(z+2)=z-18 | | x^2+(3x^2)=20 | | 5x=19.5 | | -2(5-h)=-2 | | w^2+5w-66= | | 7(y-6)=6y-16 | | 2a^2-3ab+b^2=0 | | -2(a+4)+8= | | 3+(2y+3)-4y=3 |